2022
DOI: 10.3390/molecules27123953
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal MicroRNA as Biomarkers for Diagnosing or Monitoring the Progression of Ovarian Clear Cell Carcinoma: A Pilot Study

Abstract: Ovarian cancer is the most common cause of gynecological malignancy-related mortality since early-stage disease is difficult to diagnose. Advanced clear cell carcinoma of the ovary (CCCO) has dismal prognosis, and its incidence has been increasing in Japan, emphasizing the need for highly sensitive diagnostic and prognostic CCCO biomarkers. Exosomal microRNAs (miRNAs) secreted by tumor cells are known to play a role in carcinogenesis; however, their involvement in ovarian cancer is unclear. In this study, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Although free miRNAs can be detected in the circulation, the protective effect of exosomal membranes contribute to its stability (68). Indeed, exosomal miRNAs have been proposed as biomarkers for OC (80, 81). And, adipocyte derived exosomes have been successfully detected in blood (65).…”
Section: Discussionmentioning
confidence: 99%
“…Although free miRNAs can be detected in the circulation, the protective effect of exosomal membranes contribute to its stability (68). Indeed, exosomal miRNAs have been proposed as biomarkers for OC (80, 81). And, adipocyte derived exosomes have been successfully detected in blood (65).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the presence of cancer-specific miRNAs in OCC. In these studies, miRNAs were extracted directly from cell lines and tissues, or from EVs secreted by cell lines [ 25 , 26 , 27 ]. Wyman et al compared miRNAs extracted from ovarian serous, endometrial, and clear cell carcinoma tissues with those extracted from normal ovarian surface epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Horie et al extracted and profiled miRNAs from EVs from four histological types of ovarian cancer cell lines (serous, endometrial, mucinous, and clear cells). They reported that three miRNAs (miR−21−5p, miR29a−3p and miR−30d−5p) were highly expressed in OCC [ 27 ]. In the current study, the expression levels of miR−200c−3p, miR−200a−3p, miR200b−3p, miR−200b−5p, miR−200a−5p, miR−30a−5p, miR−30b−5p, and miR−21−5p in Te-EVs extracted from OCC tissues were significantly higher than those in normal ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are a promising source of cancer biomarkers. In OC, it supports early detection of it. Exosome association in OC biomarker research is explained in Figure .…”
Section: Texs Are a Source Of Ovarian Cancer Biomarkersmentioning
confidence: 99%